Investigation on Species Composition of Plant Community at Tad Xai at Phou Khao Khouay National Park, Lao PDR - Soukhavong, Metmany; Yong, Liu; Nanthavong, Khamseng; Millet, Jérôme (Our Nature, 2013)
Phou Khao Khouay (PKK) National Park is one of the 21 National Parks in Lao PDR that supports high biodiversity. The plant community was represented by 62 families, 145 species and 1,221 tree size individuals in 50×50 m2 plots. The largest species in terms of individual number were Hydnocarpus ilicifolia, Hopea spp. and the largest families in terms of species number were Rubiaceae and Dipterocarpaceae. A total 24 families, 33 species and 91 sapling individuals were found in the 10×10 m2 sapling plots, the largest species were Rinorea boissieui, Ailanthus triphysa and Hopea spp. and the largest families were Dipterocarpaceae and Myrtaceae. In the seedling quadrat, there were 88 families, 153 species and 1,586 seedling size individuals in 2×2 m2 plots, the largest species were Hopea spp., Hopea ferrea and spp. (leguminoceae), the largest families were Rubiaceae, Annonaceae and Dipterocarpaceae. Diversity was found very high in tree and seedling was significantly higher than that of sapling, but no significant difference between tree and seedling. The largest tree height and maximum mean diameter at breast height (DBH) belonged to the family of Dipterocarpaceae. Canopy cover of Diperocarpaceae was highest (35%) in study area. Lauraceae and other 6 families had lowest crown cover around 5%. The result of this study indicated the pattern of species composition in plant community assembly and density, diversity, abundance for the vegetation layers. DOI: http://dx.doi.org/10.3126/on.v11i1.8237 Our Nature Vol.11(1) 2013: 1-10